Sukoharjo District Regional Development Policy in The Implementation of Decentralization and Regional Autonomy - Fery Dona (Veteran Justice Journal, 2019)
This research aims to find out how the policies of the district government of Sukoharjo in supporting the implementation of decentralization and regional autonomy,regions in the context of decentralization and regional autonomy. This research uses empirical research. In empirical research, what is examined initially is secondary data, and then it is continued with research on primary data in the field. Data analysis using qualitative descriptions, the results of qualitative data processing is described by the sentence separated by categories to obtain conclusions. Then the results of the analysis serve as answers to the problems raised. The results of the study show that the Government of Sukoharjo Regency's policy in supporting the implementation of decentralization and regional autonomy, among others Establishing Regional Regulation of Sukoharjo District Number 3 of 2010 concerning Long-term Regional Development Plans Year 2005-2025, Establishing Regional Regulation of Sukoharjo District Number 10 of 2010 Concerning Development Plans Medium-Term Regional Year 2016-2012, Establishing Regulation of Sukoharjo Regent Number 40 Year 2018 Regarding the Work Plan of the Regional Government of Sukoharjo Regency in 2019. Then also obtained the results of problems in regional development in the context of the implementation of decentralization and regional autonomy, among others, there is an imbalance of community income and between regions , poverty, not yet optimal workforce social security, lack of education, optimal implementation of the health service system, a large number of population growth and movement, unhealthy and less organized settlements, are still limited over clean water sources, environmental pollution, investment climate, empowerment of UMKM-Cooperatives that have not been optimal, have not received attention related to food security, not yet optimal implementation of bureaucratic reforms, not yet optimal empowerment of women and child protection, political development is not optimal, transportation conditions are not optimal , and disaster vulnerability. Keywords: Policy, Local Government, Disaster Vulnerability